Occupational health risk assessment and risk monetization based on xylene exposureMendeley Data - Fei Li; Boshen Wang; Baoli Zhu (Ecotoxicology and Environmental Safety)
The risk evaluation of occupational exposure to xylene was conducted to provide a basis for the formulation of policies on the prevention and control of occupational hazards of xylene and to fill the gap in this field. In this study, a number of xylene-related companies in seven industries from 2020 to 2023 were collected as research subjects, and the health risks caused by xylene exposure were evaluated using the EPA model designated by the U.S. Environmental Protection Agency, the Singapore Semi-Quantitative Risk Assessment Model (MOM), and the International Council on Mining and Metals (ICMM) Occupational Health Risk Assessment Model. Subsequently, a risk monetization method was used to convert the health risks of xylene exposure into currency. the results of the study showed that the EPA and MOM models were more reasonable and could accurately identify occupational health risks due to xylene exposure, while the ICMM model overestimated the health risks due to xylene exposure by assessing the risk level of all industries as level 4 or higher. Incorporating the number of people on the job into the risk assessment can differentiate the number of people involved in the health risks caused by xylene exposure, which is more conducive to the adoption of targeted preventive and control measures. The risk monetization model can provide a more intuitive view of the direct economic losses that may be caused by occupational exposure to xylene, which can help the relevant authorities to formulate strategies for the prevention and control of xylene hazards, and also provide a strong support for occupational damage compensation.